Age-Dependent Immune Events during HBV Infection from Birth to Adulthood: An Alternative Interpretation - Bertoletti, Antonio; Hong, Michelle (Frontiers in Immunology, 2014)
Immune responses change during the life of an individual. While this concept has been well accepted for adaptive immunity, only recently it is becoming clear that the innate immune responses also acquire distinct features in different phases of life. We believe that this concept can offer a different interpretation of the pathological manifestations that can be observed in HBV-infected subjects during the patient’s life. Here, we will review the age-related immunopathological features of HBV infection and discuss how the different virological and clinical manifestations might be linked to the developmental pathway of the immune system from newborns to adults. We will discuss how the age of patients can affect the degree of inflammatory responses, but not the levels of antiviral specific immunity. We then propose that the different clinical manifestations occurring during the natural history of HBV infection are related to the host ability to trigger an inflammatory immune response.